Peran Katekis Dalam Membina Iman Kaum Muda Sebagai Upaya Meningkatkan Kehidupan Menggereja - Vinsensius Septa Wardana; Intan Sakti Pius X (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The development of the Church is not only because of its leaders, but also develops thanks to the active role of church members, especially young people who are expected to play an important role in developing the church from time to time with the help of Church members as well. The purpose of this research is to encourage and motivate young people to be able to actively participate in church activities, and to make young people realize that they have an important role in developing the church and also to encourage them to have a spirit of service. This type of research uses descriptive research, where the data that has been collected comes from expert data. Descriptive research is research that seeks to describe a symptom, event, incident that is happening at the present time. Observation techniques in this method are carried out by describing the data that has been collected from library research, where this research is carried out with library sources and discusses some of the theories that are reviewed. The results of the study concluded that building faith in a young person is very important because it has useful benefits and meanings. Young people must also have someone to guide the faith, namely a catechist himself. So that young people: can build a noble and commendable youth personality.